2020
DOI: 10.3390/jcm9061939
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictive Ability of Procalcitonin of Acute Kidney Injury among Critically Ill Patients

Abstract: It is unclear whether serum procalcitonin (PCT) levels rise in patients with acute kidney injury (AKI), and it is also unclear whether the elevation of PCT levels in this setting is independent of the existence of infection and impaired renal clearance. We conducted a retrospective study in a regional teaching hospital in Taiwan to evaluate the AKI-predictive ability of serum PCT among critically ill patients. We enrolled 330 patients (mean age, 70.5 ± 16.4 years; 57.0% men) who were admitted to the intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
4
10
0
Order By: Relevance
“…Recent studies have shown that viral infections may play a pivotal role in the development of secondary GN as well as PGN, such as IgA nephropathy or membranoproliferative GN [36][37][38][39]. To this end, our studies demonstrate the association of the presence of EBV DNA copies in the peripheral blood with the expression of PD-1 and PD-L1 antigens on the surface of circulating lymphocytes.…”
Section: Discussionsupporting
confidence: 57%
“…Recent studies have shown that viral infections may play a pivotal role in the development of secondary GN as well as PGN, such as IgA nephropathy or membranoproliferative GN [36][37][38][39]. To this end, our studies demonstrate the association of the presence of EBV DNA copies in the peripheral blood with the expression of PD-1 and PD-L1 antigens on the surface of circulating lymphocytes.…”
Section: Discussionsupporting
confidence: 57%
“…We also found that serum Gal-3 levels obtained at ICU admission were associated with subsequent AKI, as were two previously studied biomarkers of kidney injury, CysC and PCT [ 50 52 ]. Further, Gal-3 levels predicted subsequent development of S-AKI after controlling for age and APACHE II score.…”
Section: Discussionsupporting
confidence: 77%
“…We also found that serum Gal-3 levels obtained at ICU admission were associated with subsequent AKI, as were two previously studied biomarkers of kidney injury, CysC and PCT [50][51][52]. Further, Gal-3 levels predicted subsequent development of S-AKI after controlling for AGE and APACHE II score.…”
Section: Discussionsupporting
confidence: 73%